2020
DOI: 10.7570/jomes20006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soy Foods in Postmenopausal Women: A Focus on Osteosarcopenia and Obesity

Abstract: Chronic diseases in postmenopausal women are caused by rapid changes in hormones and are accompanied by rapid changes in body composition (muscle, bone, and fat). In an aging society, the health of postmenopausal women is a social issue, and people' s interest in ingesting high-quality protein is increasing in order to maintain a healthy body composition. This review aims to summarize the efficacy of soy foods and their impact on body composition. The soy protein and isoflavones contained in soy foods can impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…The results of our study are consistent with these reports. We found that AET combined with ISP supplementation improved the body weight, BMI, PBF, and PLBM more effectively than AET alone (all effect sizes > 0.8, Table 3), which may be related to the sustained decrease in appetite, enhanced satiety, and energy expenditure, and promotion of lipid metabolism due to the regulation of the expression of sterol regulatory element-binding proteins after ISP intake [7,13,52]. These findings indicate that ISP is an effective postexercise supplementation that can induce positive improvements in the body composition of women.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The results of our study are consistent with these reports. We found that AET combined with ISP supplementation improved the body weight, BMI, PBF, and PLBM more effectively than AET alone (all effect sizes > 0.8, Table 3), which may be related to the sustained decrease in appetite, enhanced satiety, and energy expenditure, and promotion of lipid metabolism due to the regulation of the expression of sterol regulatory element-binding proteins after ISP intake [7,13,52]. These findings indicate that ISP is an effective postexercise supplementation that can induce positive improvements in the body composition of women.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, small amounts of dietary protein reduce the breakdown of muscle protein, whereas large amounts of protein supplementation stimulate the synthesis of muscle protein [12]. Protein supplementations allow for higher protein intake, and consuming adequate ISP can result in decreased body fat and weight; thus, they can be used by exercising individuals who require more protein to maintain lean body mass and accelerate fat loss [4,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Men tend to have visceral obesity, which is associated with increased cardiometabolic risk; women tend to have gynoid obesity in which most of the fat is subcutaneous, which has a weaker effect on cardiometabolic risk [ 56 , 57 ]. However, estrogen deficiency in postmenopausal women tends to cause visceral obesity [ 58 , 59 ]. SI and its metabolites can bind to estrogen and androgen receptors to exert biological effects of estrogen [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information on the excess intake of soy. But no more than 25 grams a day of soy is recommended [290].…”
Section: Toxicological Aspectsmentioning
confidence: 99%